Optimal intergenerational redistribution and strategic incentives with two countries and endogenous fertility: Theory and application to the European Union - Martin Kolmar (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
Intergenerational redistribution is one of the major aims of national welfare states that have to prove their reliability in a world of internationally integrated goods and factor markets. In this paper, we analyse the conditions for the existence of steady-state equilibria and the (Pareto-) optimal structure of national PAYG systems in a two-country model with endogenous fertility. Secondly we demonstrate that there are strategic incentives for national authorities to deviate from the optimal pension scheme even without labor mobility, which is the common source of inefficiencies in models of interregional social competition. They have two sources of strategic behavior in the model: One is an interest externality, the other one is a growth externality. This second externality shows that these incentives exist even with an exogenous interest rate. Policy implications for the European Union are discussed.
Keywords: 330; Gesetzliche Rentenversicherung; Umlageverfahren; Spillover-Effekt; Offene Volkswirtschaft; Familienökonomik; Regionale Wachstumstheorie; Spieltheorie; Theorie; EU-Staaten